Landslides and debris flows of 19-21 July 1993 in the Agra Khola watershed of Central Nepal - Thapa, P. B.; Dhital, M. R. (Journal of Nepal Geological Society, 2000)
High intensity rainfall of 19-21 July 1993 triggered off a large number of mass movements in the Agra Khola watershed of Central Nepal. It caused a heavy loss of human lives and property. Landslides were distributed mainly in the upper part of the watershed, especially in the vicinity of Chisapani, Chaubas, Dandabas, and Chhap. Main types of mass movement were rockslides, soils slides, and complex failures. About 51% of them were soil slides and 18% were rockslides. Among the rockslides, 4% were deep-seated rotational slides. Large deep-seated rockslides were common on the north-facing dip slopes, whereas shallow slides were observed on the counter dip slopes and in the area occupied by granite. Soil slides occurred on slopes covered by 1-6 m deep colluvium and/or residual soils. The highest percentage of landslides was found in the Kulikhani Formation and on slopes of 25°-45°. The material from landslides contributed to a huge amount of debris, which was deposited on cultivated land. The debris formed up to 5 m high terraces along the rivers. The upper reaches of the Agra Khola and Chalti Khola are the main hazardous areas.